Transport properties in aggregates of Nb nanowires templated by carbon nanotube films. (August 2016) - Salvato, M.; Cirillo, C.; Fittipaldi, R.; Prischepa, S.L.; Vecchione, A.; De Nicola, F.; Castrucci, P.; De Crescenzi, M.; Scarselli, M.; Attanasio, C.
Abstract: Films of multiwall carbon nanotubes (CNTs), arranged on Si/SiO2 substrates, are used as templates for Nb films with thickness in the range 3–50 nm deposited by sputtering. The resulting aggregates show normal state and superconducting properties similar to those observed in networks of superconducting nanowires (SNW) obtained by other methods. Decreasing the Nb thickness, when the normal state resistance becomes larger than the quantum resistance, a superconductor-insulator transition is observed. Moreover, thermally activated phase slips in thicker samples, evolving in quantum phase slips in thinner nanowires, are observed in the superconducting state. The experimental results indicate that the template method based on CNTs is a promising alternative to the much more expensive nanolithography techniques for obtaining SNWs. Even more important, they indicate CNT films as versatile elements in nanostructured electronic devices.